Interaction between bedding and sleeping position in the sudden infant death syndrome: a population based case-control study. Issue 6743 (14th July 1990) - Fleming, P J; Gilbert, R; Azaz, Y; Berry, P J; Rudd, P T; Stewart, A; Hall, E
Abstract : OBJECTIVE–To determine the relation between sleeping position and quantity of bedding and the risk of sudden unexpected infant death. DESIGN–A study of all infants dying suddenly and unexpectedly and of two controls matched for age and date with each index case. The parents of control infants were interviewed within 72 hours of the index infant's death. Information was collected on bedding, sleeping position, heating, and recent signs of illness for index and control infants. SETTING–A defined geographical area comprising most of the county of Avon and part of Somerset. SUBJECTS–72 Infants who had died suddenly and unexpectedly (of whom 67 had died from the sudden infant death syndrome) and 144 control infants. RESULTS–Compared with the control infants the infants who had died from the sudden infant death syndrome were more likely to have been sleeping prone (relative risk 8.8; 95% confidence interval 7.0 to 11.0; p less than 0.001), to have been more heavily wrapped (relative risk 1.14 per tog above 8 tog; 1.03 to 1.28; p less than 0.05), and to have had the heating on all night (relative risk 2.7; 1.4 to 5.2; p less than 0.01). These differences were less pronounced in the younger infants (less than 70 days) than the older ones. The risk of sudden unexpected death among infants older than 70 days, nursed prone, and with clothing and bedding of total thermal resistance greater than 10 tog was increased by factors of 15.1 (2.6 to 89.6) and 25.2 (3.7 to 169.0) respectively compared with the risk in infants of the same age nursed supine or on their side and under less than 6 tog of bedding. CONCLUSIONS–Overheating and the prone position are independently associated with an increased risk of sudden unexpected infant death, particularly in infants aged more than 70 days. Educating parents about appropriate thermal care and sleeping position of infants may help to reduce the incidence of the sudden infant death syndrome.